2004
DOI: 10.1016/j.cell.2004.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of DDX3 DEAD Box RNA Helicase for HIV-1 Rev-RRE Export Function

Abstract: A single transcript in its unspliced and spliced forms directs the synthesis of all HIV-1 proteins. Although nuclear export of intron-containing cellular transcripts is restricted in mammalian cells, HIV-1 has evolved the viral Rev protein to overcome this restriction for viral transcripts. Previously, CRM1 was identified as a cellular cofactor for Rev-dependent export of intron-containing HIV-1 RNA. Here, we present evidence that Rev/CRM1 activity utilizes the ATP-dependent DEAD box RNA helicase, DDX3. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
650
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 503 publications
(682 citation statements)
references
References 60 publications
30
650
2
Order By: Relevance
“…DDX3 as a component of initial RNA sensor RIG-I and MDA5 are IFN-inducible proteins, only traces of which exist in an early phase (o2 h) in the cytoplasm where viral RNA replicate. Previous reports showed that DDX3 binds RNA of poly rA or duplexed RNA [13,14], and our protein analysis solidified this issue: DDX3 efficiently bound polyI:C and stem-loop RNA of viral origin in a solution (data not shown). DDX3 as well as IPS-1 were expressed even without any stimulation ( Fig.…”
Section: Ddx3 Promotes Ips-1-mediated Ifn-b Promoter Activationsupporting
confidence: 78%
See 2 more Smart Citations
“…DDX3 as a component of initial RNA sensor RIG-I and MDA5 are IFN-inducible proteins, only traces of which exist in an early phase (o2 h) in the cytoplasm where viral RNA replicate. Previous reports showed that DDX3 binds RNA of poly rA or duplexed RNA [13,14], and our protein analysis solidified this issue: DDX3 efficiently bound polyI:C and stem-loop RNA of viral origin in a solution (data not shown). DDX3 as well as IPS-1 were expressed even without any stimulation ( Fig.…”
Section: Ddx3 Promotes Ips-1-mediated Ifn-b Promoter Activationsupporting
confidence: 78%
“…Previous reports [13,14] and our RNA-binding analysis also speculated that one of the RNA-capture proteins is DDX3 since DDX3 tightly binds polyI:C and dsRNA in fluid phase. These RNA-capture proteins may have a role in the IPS-1-involving molecular platform in cells with early virus infection when only a trace RIG-I protein is expressed.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…As a member of DEAD box RNA helicase family, DDX3 is a nucleo-cytoplasmic shuttling protein and possesses RNA-dependent ATPase/helicase activity (You et al, 1999;Yedavalli et al, 2004). Although the precise biological function of DDX3 remains elusive, it has been reported that DDX3 is involved in many cellular processes.…”
mentioning
confidence: 99%
“…Additionally, owing to its association with functional spliceosomes, DDX3 has been suggested to be involved in RNA splicing (Zhou et al, 2002). Most interestingly, DDX3 is not only required for HIV Rev-RRE export (Yedavalli et al, 2004), but also interacts with hepatitis C virus (HCV) core protein (Mamiya and Worman, 1999;Owsianka and Patel, 1999;You et al, 1999), suggesting a role in the life cycle or pathogenesis of certain viruses. More recently, we demonstrated that DDX3 harbors tumor-growth suppressive ability and can modulate the transcriptional activity of the p21 waf1/cip1 promoter through physical interaction with Sp1 (Chao et al, 2006).…”
mentioning
confidence: 99%